2020
DOI: 10.1002/lary.29060
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–Phenotype Correlation of Tracheal Cartilaginous Sleeves and Fgfr2 Mutations in Mice

Abstract: Objectives: To characterize tracheal cartilage morphology in mouse models of fibroblast growth factor receptor (Fgfr2)related craniosynostosis syndromes. To establish relationships between specific Fgfr2 mutations and tracheal cartilaginous sleeve (TCS) phenotypes in these mouse models. Methods: Postnatal day 0 knock-in mouse lines with disease-specific genetic variations in the Fgfr2 gene (Fgfr2 C342Y/C342Y , Fgfr2 C342Y/+ , Fgfr2 +/Y394C , Fgfr2 +/S252W , and Fgfr2 +/P253R) as well as line-specific controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Mice heterozygous or homozygous for activating mutations in Fgfr2 (p.C342Y) that cause Crouzon syndrome fail to segment tracheal cartilage resulting in a rigid tracheal sleeve. Prior to segmentation, mutant mice show increased chondrocyte proliferation (Hines et al, 2019; Lam et al, 2021; Peskett et al, 2017).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Mice heterozygous or homozygous for activating mutations in Fgfr2 (p.C342Y) that cause Crouzon syndrome fail to segment tracheal cartilage resulting in a rigid tracheal sleeve. Prior to segmentation, mutant mice show increased chondrocyte proliferation (Hines et al, 2019; Lam et al, 2021; Peskett et al, 2017).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Most of the work with craniosynostosis-associated genetic variants have focused on the bony skull of mouse models for craniosynostosis, or on human cell lines to demonstrate how specific variants alter the processes of proliferation, differentiation, apoptosis, and/or polarity of osteoblast lineage cells as they differentiate. Exceptions include a study of Fgfr2c C342Y/C342Y mice suggesting that many phenotypic aberrations stem from a primary failure of mesenchymal condensation contributing to aberrant cartilage and bone ( Peskett et al, 2017 ), observations of enhanced tracheal cartilage formation in Fgfr2 mouse lines suggesting that abnormal chondrogenesis occurred ( Lam et al, 2021 ; Wang et al, 2005 ), and studies that demonstrate cartilage-autonomous effects of Fgfr2 variants on the septum nasi and other facial cartilages ( Holmes et al, 2018 ; Kim et al, 2021 ). Holmes et al, 2018 found nasal cavity volume reduction and cartilage thickening to contribute significantly to the prenatal midface phenotype in two Apert syndrome mouse models ( Fgfr2 +/S252W and Fgfr2 +/P253R ) and the Crouzon mouse model used here, but that structural and cellular changes resulting in midfacial dysgenesis differ among specific Fgfr2 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the work with craniosynostosis-associated genetic variants have focused on the bony skull of mouse models for craniosynostosis, or on human cell lines to demonstrate how specific variants alter the processes of proliferation, differentiation, apoptosis, and/or polarity of osteoblast lineage cells as they differentiate. Exceptions include a study of Fgfr2c C342Y/C342Y mice suggesting that many phenotypic aberrations stem from a primary failure of mesenchymal condensation contributing to aberrant cartilage and bone (Peskett et al, 2017), observations of enhanced tracheal cartilage formation in Fgfr2 mouse lines suggesting that abnormal chondrogenesis occurred (Lam et al, 2021; Wang et al, 2005), and studies that demonstrate cartilage-autonomous effects of Fgfr2 variants on the septum nasi and other facial cartilages (Holmes et al, 2018; Kim et al, 2021). Holmes et al (Holmes et al, 2018) found nasal cavity volume reduction and cartilage thickening to contribute significantly to the prenatal midface phenotype in two Apert syndrome mouse models ( Fgfr2 +/S252W and Fgfr2 +/P253R ) and the Crouzon mouse model used here, but that structural and cellular changes resulting in midfacial dysgenesis differ among specific Fgfr2 variants.…”
Section: Discussionmentioning
confidence: 99%